Standards for reporting on surgery for chronic pancreatitis: a report from the International Study Group for Pancreatic Surgery (ISGPS) - Siriwardena, Ajith; Windsor, John; Zyromski, Nicholas; Marchegiani, Giovanni; Radenkovic, Dejan; Morgan, Catherine; Passas, Ioannis; Olah, Attila; Conlon, Kevin C.; Smith, Martin; Busch, Olivier; Baltatzis, Minas; et al. (Surgery, 2020)
Background: The International Study Group for Pancreatic Surgery provides globally accepted definitions for reporting of complications after pancreatic surgery. This International Study Group for Pancreatic Surgery project aims to provide a standardized framework for reporting of the results of operative treatment for chronic pancreatitis. Methods: An International Study Group for Pancreatic Surgery project circulation list was created with pre-existing and new members and including gastroenterologists in addition to surgeons. A computerized search of the literature was undertaken for articles reporting the operative treatment of chronic pancreatitis. The results of the literature search were presented at the first face-to-face meeting of this International Study Group for Pancreatic Surgery project group. A document outlining proposed reporting standards was produced by discussion during an initial meeting of the International Study Group for Pancreatic Surgery. An electronic questionnaire was then sent to all current members of the International Study Group for Pancreatic Surgery. Responses were collated and further discussed at international meetings in North America, Europe, and at the International Association of Pancreatology World Congress in 2019. A final consensus document was produced by integration of multiple iterations. Results: The International Study Group for Pancreatic Surgery consensus standards for reporting of surgery in chronic pancreatitis recommends 4 core domains and the necessary variables needed for reporting of results: clinical baseline before operation; the morphology of the diseased gland; a new, standardized, operative terminology; and a minimum outcome dataset. The 4 domains combine to give a comprehensive framework for reports. Conclusion: Adoption of the 4 domains of the International Study Group for Pancreatic Surgery reporting standards for surgery for chronic pancreatitis will facilitate comparison of results between centers and help to improve the care for patients with this debilitating disease.
Gesehen am 27.04.2021